Adiposity and attained height in adolescents: a longitudinal analysis from the LabMed Physical Activity Study - Rafaela Rosário (2019)
Background: To investigate the associations between adiposity and attained height over a 2-year period in healthy adolescents. Methods: One thousand and seventeen adolescents aged 12-18 years participated in this cohort study; 893 (87.8%) were reevaluated 1 year later (T2) and 734 (72.2%) subjects 2 years later (T3). Body fat and anthropometry were measured according to standardized procedures. Socioeconomic status, pubertal stage and lifestyles determinants were gathered and used as confounders. Prospective associations between adiposity and height were examined using generalized linear models. Results: Greater adiposity at T1 was significantly associated with a lower attained height over time, when adjusting for confounders, which varied between 0.03 and 1 cm in T2 and 0.1 and 1 cm T3. Conclusions: Excess of adiposity in early adolescence may exert an effect on attained height in late adolescence. This study supports future lifestyles intervention studies aiming at preventing overweight and obesity and improving attained height.